Analysis of Legal Protection on Employment Contracts Between Owner and Ship Crew at One of PT. Pelayaran Samudra Kancana - Hendriyanto, Saini; Handayani, Pristika; Hadiyanto, Alwan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The problem of sailor protection in its implementation is still far from expectations. This is evident in the practice of employment in the maritime sector, there are still things that are not in accordance with what has been stipulated in the Employment Law. Where employers still make their own rules for the benefit of the company without considering the rights of their workers. This research used the qualitative approach which is a research approach that aims to understand phenomena about what is experienced by research subjects, such as behavior, perception, motivation, actions and so on holistically and by means of description in the form of words and language in a specific context. Based on the results of the study, it was concluded that state protection of maritime workers is still weak and slow from maritime security and safety threats. Other issues such as wages, maritime work contracts, Indonesian maritime professional certification, strikes, unilateral layoffs, severance pay, freedom of association of maritime workers, and foreign sailor workers are issues that have been problems for both shipping companies and Indonesian sailor workers. The state must be fair in the payroll system, the internal supervision function must still have external supervision, there needs to be a ministerial or presidential decision on the salary standards of Indonesian sailors.